Estimating the non-thermal inactivation of Listeria monocytogenes in fermented sausages relative to temperature, pH and water activity. (February 2015) - Mataragas, M.; Rantsiou, K.; Alessandria, V.; Cocolin, L.
Abstract: Data relative to in situ Listeria monocytogenes inactivation in fermented sausages were collected from 13 individual studies found in the literature. Inactivation rates were extrapolated and used to develop a predictive model to evaluate the relative effects of pH, water activity (aw ) and temperature on L. monocytogenes fate during fermentation and ripening. Temperature explained ca. 60% of the data variability, while pH and aw only a small part. Temperature alone may not be sufficient to cause pathogen's inactivation, but inactivation rate is dominated by temperature when pH and aw are in the range which prevent L. monocytogenes growth. A predictive model based on two Arrhenius equations (ln[inactivation rate] = − 25.71 − [− 0.6829 / (8.314 × T)] for fermentation; and ln[inactivation rate] = − 44.86 − [− 1.219/(8.314 × T)] for ripening) was developed. The model can be used to quantify the effect of temperature and/or time changes on fermented sausage safety. The advantages and limitations of the model are discussed. Highlights: Meta-analysis of L. monocytogenes inactivation in fermented sausages was performed. The relative effect of temperature, pH and aw was evaluated. Temperature explained ca. 60% of the variance while pH and aw only a small part. A predictive model for the relative effect of temperature was developed. Model is useful for conservative predictions of the fermented sausage safety